Методи протидії несанкціанованому запису мови - Моісеєнко, М. А. (ХНУРЕ, 2024)
This article describes the main methods of protecting speech information from leakage. All methods can be divided into two categories, namely methods for detecting and suppressing these devices. Suppression methods are considered the most effective in our time due to a higher level of reliability. The most common method of suppressing embedded devices is the acoustic method; it is considered the most universal in application and provides a relatively high level of protection.
Keywords: несанкціанований запис мови